Analisis Activity Based Costing sebagai Alternatif Perhitungan Tarif Jasa Rawat Inap pada RSUD Lewoleba - Sesilia Anggraeini Sili; Petrus E. de Rosari; Yohanes Demu (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
This study aims to determine the calculation of inpatient service rates using the Activity Based Costing method at the Lewoleba Regional General Hospital. in determining and calculating the cost price. The data for this study used secondary data supplemented with data obtained through interviews from various sections at Lewoleba Regional Hospital, then data processing and analysis were carried out. The data analysis used was a difference test using the Paired Sample T-Test to find out whether or not there is a difference in the inpatient service rates set by Lewoleba Regional Hospital with the basic price of inpatient rates using the activity based costing method . The results of the Activity Based Costing test for Class I, Class II , and Class III obtained a profit of above 70 %, namely 74.4 %, 75.8%, And 21.6 %. So that can it is said that Hospital​ Lewoleba in determining the inpatient rates for each class is too high or too low Lots to obtain profit especially on class II Which has the biggest advantage and is much bigger than the profit expected by the house Sick. The conclusion that can be drawn based on the results of the study above is that there is a difference between the inpatient rates set by Ru Lewoleba and the basic price of inpatient rates generated using the Activity Based Costing method. Suggestions related to the results of this study are that Lewoleba Hospital needs to review its inpatient rate determination method by trying to apply the Activity Based Costing method cost calculation system in order to be able to produce more appropriate rates.